Single and two-phase flows on chemical and biomedical engineering - Dias, Ricardo P. (2014)
Single or two-phase flows are ubiquitous in most natural process and engineering systems. Examples of systems or process include packed bed reactors, either single phase or multiphase, absorber and adsorber separation columns, filter beds, plate heat exchangers, flow of viscoelastic fluids in polymer systems, or the enhanced recovery of oil, among others. In each case the flow plays a central role in determining the system or process behaviour and performance. A better understanding of the underlying physical phenomena and the ability to describe is crucial to design, operate and control processes involving the flow of fluids, ensuring that they will be more efficient and cost effective. Growing areas such as microfluidics, nanomedicine and the modelling and simulation of complex flow in living systems such as the blood flow in microvascular networks rely upon a good description of the flow. One way of studying the blood flow behavior is in the context of blood flow in large arteries, and another is in small vessels. In the former case, blood may be treated as a homogenous fluid and Newtonian constitutive equations are generally accepted as a good approximation to express the rheological property of blood. In small vessels, however, the scale of generated flow field sometimes becomes comparable to the scale of a blood cell. The chapters from the area of biomedical engineering will describe several physiological and pathological events that happen in both large and small vessels. Recent advances either in computational and experimental techniques are improving the existing knowledge of single and multiphase flows in engineering and physical systems of interest. This book reviews the state of the art and recent advances in various key areas of fluid mechanics and transport phenomena in the fields of chemical and biomedical engineering.